2012
DOI: 10.1177/1098612x12451797
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic en bloc thoracic duct sealing and partial pericardectomy for the treatment of chylothorax in two cats

Abstract: Two cats with intractable idiopathic chylothorax and a history of unsuccessful medical management were treated thoracoscopically with en bloc thoracic duct sealing and subtotal pericardectomy using a bipolar feedbackcontrolled vessel sealing device. No surgical complications were observed. Twenty-four and 26 months after surgery, both cats were free of thoracic effusion and clinical signs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 17 publications
0
16
0
1
Order By: Relevance
“…Most of these procedures have been reported in medium to large breed dogs. In cats and small breeds of dog (<10 kg), few descriptions of thoracoscopic surgery exist although thoracic duct ligation in combination with pericardectomy has been performed in small dogs and cats for treatment of chylothorax …”
mentioning
confidence: 99%
“…Most of these procedures have been reported in medium to large breed dogs. In cats and small breeds of dog (<10 kg), few descriptions of thoracoscopic surgery exist although thoracic duct ligation in combination with pericardectomy has been performed in small dogs and cats for treatment of chylothorax …”
mentioning
confidence: 99%
“…An alteration in surgical technique that may have decreased lymphatic leakage would have been to avoid direct manipulation of the thoracic duct branches by sealing all tissues en bloc, dorsal to the aorta and ventral to the sympathetic trunk. This en bloc transection technique with a bipolar vessel‐sealing device has been described in 2 clinical cases of feline chylothorax in which there was no chyle leakage at the time of surgery, and resolution of their chylous effusion was confirmed by recheck thoracic radiographs . Thoracoscopic subtotal pericardectomy was also performed in both cases along with omentalization of the thoracic cavity in 1 of the cases .…”
Section: Discussionmentioning
confidence: 99%
“…Results from these studies only report the outcomes of the VATS approach in 13 dogs with IC but results compare very favourably with the results obtained with this combination of therapies using an open thoracic approach. Recently a report of two cats with IC treated with a VATS approach was published with resolution of signs seen in both cases (Haimel et al 2012). Cisterna chyli ablation has emerged as an additional procedure favoured by some surgeons and in one prospective randomised study was shown to have Recent advances in minimally invasive surgery (Applied Medical Inc.) amongst others (Runge 2012).…”
Section: Minimally Invasive Management Of Idiopathic Chylothoraxmentioning
confidence: 99%
“…Recently a report of two cats with IC treated with a VATS approach was published with resolution of signs seen in both cases (Haimel et al . ). Cisterna chyli ablation has emerged as an additional procedure favoured by some surgeons and in one prospective randomised study was shown to have improved results compared to a control group treated with thoracic duct ligation and pericardiectomy using an open surgical approach (McAnulty ).…”
Section: Introductionmentioning
confidence: 97%